Comparative evaluation of the canal transportation after retreatment with Solite RS3 and Protaper Universal retreatment files: a nano computed tomography study - Sairaman , Sruthi; Solete , Pradeep; Jeevanandam , Ganesh; Sena, Divya; Teja, Kavalipurapu Venkata; Mustafa, Mohammed (Brazilian Dental Science, 2024)
Objective: The primary objective of instrumentation during retreatment is to preserve the original curvature of the canal while removing gutta-percha. The current study assesses the canal transportation after retreatment with two different retreatment file systems. Materials and Methods: Sixty single-rooted teeth, extracted and decoronated, were obturated at a standardized root length of 16 mm. The samples were then divided into two groups, each comprising 20 single-rooted teeth. The instrumentation was performed using Solite RS3 Retreatment files for one group and ProTaper Retreatment files for the other. After both pre-operative and post-operative nano-CT scans, 3D reconstruction was conducted for analysis. Sections of the pre-operative and post-operative samples were taken at 7 mm, 5 mm, and 3 mm and 1 mm from the apex to calculate the canal transportation. Statistical analysis between the two groups was carried out using an independent t-test. Results: Solite RS3 retreatment files exhibited a statistically significant difference at all three levels (p < 0.05) when compared to ProTaper retreatment files, thus showing lesser canal transportation than the latter. Conclusion: Based on the above results, it can be concluded that Solite RS3 induced minimal canal transportation and resulted in a relatively centered preparation compared to the ProTaper Retreatment system. KEYWORDS Canal transportation; Nano-CT; Remaining dentin thickness; Retreatment; Solite RS3.